2019
DOI: 10.3389/fphar.2019.01054
|View full text |Cite
|
Sign up to set email alerts
|

Global Sensitivity Analysis of Ventricular Myocyte Model-Derived Metrics for Proarrhythmic Risk Assessment

Abstract: Multiscale computational models of the heart are being extensively investigated for improved assessment of drug-induced torsades de pointes (TdP) risk, a fatal side effect of many drugs. Model-derived metrics such as action potential duration and net charge carried by ionic currents (qNet) have been proposed as potential candidates for TdP risk stratification after being tested on small datasets. Unlike purely statistical approaches, model-derived metrics are thought to provide mechanism-based classification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 60 publications
(123 reference statements)
4
17
0
Order By: Relevance
“…Q net values found by us for the two antimalarials ( Table S31 of Supplemental files) are similar to those reported by ( Delaunois et al, 2021 ; Whittaker et al, 2021 ), along with APD-prolongation and EAD-induction effects found in other simulation studies ( Montnach et al, 2021 ; Varshneya et al, 2021 ). Although Q net provides an in-depth mechanistic interpretation of proarrhythmogenic effects ( Parikh et al, 2019 ), we found that the method requires supplementary precautions and avoiding simulated APs that actually feature EADs.…”
Section: Discussionmentioning
confidence: 99%
“…Q net values found by us for the two antimalarials ( Table S31 of Supplemental files) are similar to those reported by ( Delaunois et al, 2021 ; Whittaker et al, 2021 ), along with APD-prolongation and EAD-induction effects found in other simulation studies ( Montnach et al, 2021 ; Varshneya et al, 2021 ). Although Q net provides an in-depth mechanistic interpretation of proarrhythmogenic effects ( Parikh et al, 2019 ), we found that the method requires supplementary precautions and avoiding simulated APs that actually feature EADs.…”
Section: Discussionmentioning
confidence: 99%
“…ERG block is a sensitive but not specific measure of TdP risk, i.e. it gives few false negatives but false positives may be preventing safe drugs from entering the market [50]. The Comprehensive in vitro Pro-arrhythmia Assay (CiPA) is a new global initiative to create guidelines for the assessment of drug-induced TdP that recommends a central role for computational modeling of ion channels and in silico evaluation of compounds [19,40].…”
Section: Discussionmentioning
confidence: 99%
“…We performed global sensitivity analysis to systematically examine the influence of model input parameters on various model-derived metrics. Mean Decrease Accuracy (MDA) was used for estimation of sensitivity, as in our previous study [ 38 ]. Briefly, sensitivity analysis via MDA requires fitting a linear or non-linear regression model (e.g., linear regression model, random forest regression model, etc.)…”
Section: Methodsmentioning
confidence: 99%